Hydrologic Decision Support in the Nile Basin: Creating Status Products from the GEOGLOWS Hydrologic Model - Rachel Huber Magoffin; Riley C. Hales; E. James Nelson; Calvince Wara; Gustavious P. Williams; Andrew South; Zeleke K. Challa (Hydrology)
Effective decision-making in water resource management requires timely and reliable streamflow information. This study demonstrates how the GEOGLOWS Hydrologic Model, River Forecast System (RFS), can generate actionable hydrologic status products, focusing on a case study in the Nile River Basin. Through collaboration with stakeholders at the Nile Basin Initiative (NBI), we identify key information needs and apply standardized low flow calculations, including the Standardized Streamflow Index (SSI) and the 95th percentile (Q95) threshold, to assess stream conditions. Additionally, we apply the World Meteorological Organization’s (WMO) Hydrologic Status and Outlook System (HydroSOS) method for streams and generate the associated HydroSOS-styled graphs and maps. We present the hydrologic status products in a customized web application for stakeholders in the Nile Basin. We discuss how RFS can be applied globally to provide hydrologic information.